2015
DOI: 10.1111/jth.12917
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between rivaroxaban and antiphospholipid antibodies in thrombotic antiphospholipid syndrome

Abstract: but not with TVT/ECT at peak rivaroxaban levels, and remained LA-ve with both DRVVT reagents and TVT/ ECT at trough levels. aPL positive IgG spiking of PNP had no effect on rivaroxaban's anticoagulant action on thrombin generation or rivaroxaban anti-Xa levels. Conclusions: The TVT/ECT ratio and Textarin time were not affected even at peak rivaroxaban levels, enabling detection of LA ex vivo. aPL had no effects on rivaroxaban's anticoagulant action in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 30 publications
4
63
1
Order By: Relevance
“…Indeed, in vitro, the effects of antiphospholipid antibodies on thrombin generation are limited to prolongation of lag time and time to peak thrombin generation 31 . Our exploratory post-hoc analysis showed no significant interactions between the effects of rivaroxaban and lupus anticoagulant positivity on thrombin generation.…”
Section: Discussionmentioning
confidence: 65%
“…Indeed, in vitro, the effects of antiphospholipid antibodies on thrombin generation are limited to prolongation of lag time and time to peak thrombin generation 31 . Our exploratory post-hoc analysis showed no significant interactions between the effects of rivaroxaban and lupus anticoagulant positivity on thrombin generation.…”
Section: Discussionmentioning
confidence: 65%
“…False positivity in RIV-treated patients was illustrated previously [21][22][23][24]. Martinuzzo et al found that most RIV-treated patients presented prolonged dRVVT screen results without correction with PNP and mostly LAC ratios above the CO [21].…”
Section: Discussionmentioning
confidence: 93%
“…Martinuzzo et al found that most RIV-treated patients presented prolonged dRVVT screen results without correction with PNP and mostly LAC ratios above the CO [21]. Arachillage et al determined that false-positive LAC results were obtained starting from 250 ng/mL on using two dRVVT systems [22]. Merriman et al performed LAC analysis on 21 RIV-treated non-APS patients, which yielded a prolonged screen, mix and LAC ratio.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…TVT/ECT was considered positive if the TVT was prolonged and the normalized TVT/ECT ratio was >1.20. The TVT/ECT ratio cut‐off of 1.20 was established locally in accordance with CLSI guidelines…”
Section: Methodsmentioning
confidence: 99%